The Settlement of Domestic Violence Cases (KDRT) Based On Islamic Values and Local Wisdom - Ismayawati, Any; Sa’diyah, Zaimatus (al-'adalah, 2019)
The Settlement of Domestic Violence Cases (KDRT) Based On Islamic Values and Local Wisdom. This research explores the conflict resolution of domestic violence (KDRT) cases based on Islamic values and local wisdom. The aim is to find alternatives to solving legal problems without having to go through legal channels (litigation). Although the Government has passed Law No. 23/2004 aimed at suppressing cases of domestic violence, the regulation is still not effective in overcoming the problem. It is proven that such cases still appear in public spaces and stick out like an iceberg. The main factor causing the difficulties was due to the kinship between the victim and the perpetrator. After examining both ”al-sulh”, the methodology for resolving conflicts based on Islamic values, and “Musyawarah”, the method based on local wisdom, this research finds out that the above-two alternative solutions have several advantages compared to legal channels. The two models of the resolution, therefore, can be used as alternatives for resolving conflicts in the household, especially those accompanied by violence.